Ionic processes in urine: a study of factors which may affect the renal excretion of inorganic phosphate - Isaacson, Leon Charles (Department of Medicine, 2020)
This thesis is composed of two parts, each related to the problem of the mode of regulation of the renal excretion of inorganic phosphate. Part one presents new data concerning the hypothesis of secretion of inorganic phosphate in the dog kidney, and as such is clearly relevant to the problem cited above. Part two arose from the earlier observations suggestive of a passive transport process in the renal tubular re-absorption of inorganic phosphate, a hypothesis consistent with a physio-chemical mode of action of parathyroid hormone upon either the glomerular filtrate or the proximal renal tubular epithelium. At about the time of formulation of this hypothesis, investigations into the aetiology of renal stone formation were commenced in this laboratory, so creating an opportunity for the study of the physico-chemical structure of urine. As such a study was also clearly desirable preliminary to the further investigation of possible physico-chemical renal effects of the parathyroid hormone, it was embarked upon from this point of view. The latter investigation has yielded results of general interest, quite apart from any relevance they may have to the problem of regulation of urinary phosphate excretion, and for this reason is presented here, with Part One, under the broad title of "Ionic Process in Urine".